A multiphase interleaved boost converter with coupled inductor for fuel cell APU applications - Shih Chieh, Lai (2018)
The growing demands for electrical capacity on future more electric aircraft (MEA) has led the engine-based generators to increase in size. Many manufacturers and researchers have a strong interest in developing fuel cells for aerospace applications due to their advantage of high efficiency and their use as a medium for clean energy resources. A particular interest is in using fuel cells within the Auxiliary Power Unit (APU) - a function that is currently provided by an additional gas turbine in most aircraft. Their integration into aircraft systems is not straightforward. A particular challenge, which this thesis addresses, is the provision of a suitable power conversion system which is able to interface the fuel cell to the aircraft electrical system – taking account of the complex electrical characteristics of the fuel cell and the demanding requirements of the aircraft electrical network.